2017
DOI: 10.1111/cpr.12331
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐9 inhibits the gastric cancer cell proliferation by targeting TNFAIP8

Abstract: Our results suggested that MicroRNA-9-TNFAIP8 might represent a promising diagnostic biomarker for GC patients and could be a potential therapeutic target in the prevention and treatment of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…44 Then, TNFAIP8 overexpression was found in various tumor cells such as breast cancer cells, non-small cell lung cancer (NSCLC) cells, gastric cancer cells and so on. 45…”
Section: Tnfaip8 Basic Characteristics Of Tnfaip8mentioning
confidence: 99%
See 2 more Smart Citations
“…44 Then, TNFAIP8 overexpression was found in various tumor cells such as breast cancer cells, non-small cell lung cancer (NSCLC) cells, gastric cancer cells and so on. 45…”
Section: Tnfaip8 Basic Characteristics Of Tnfaip8mentioning
confidence: 99%
“…76 Recently, many studies on Chinese population suggested that TNFAIP8 expression was related to other tumors such as thyroid papillary carcinoma, epithelial ovarian cancer, gastric cancer and esophageal squamous cell carcinoma. 42,45,47,[77][78][79][80] A study showed that TNFAIP8 overexpression was not obviously related with the prognosis of gastric cancer patients, but it was an independent prognostic factor for disease-free survival (DFS) and overall survival (OS) in patients with intestinal type of gastric cancer. 49 Recent studies related to TNFAIP8 and gastric cancer had focused on miRNAs, and it was well known that abnormal regulation of miRNAs could affect proliferation, apoptosis, invasion and metastasis in the development of tumors.…”
Section: Tnfaip8 and Malignant Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs act as key regulators in a wide variety of physiological and pathological processes, such as cell proliferation, cycle, differentiation, apoptosis, metabolism and death (15)(16)(17). An increasing number of studies reported miRNA dysregulation in various kinds of human cancers, such as gastric cancer (18), glioma (19), lung cancer (20), bladder cancer (21) and RB (22). The abnormally expressed miRNAs are involved in progression and development of various cancers and serve as oncogenic and tumour suppressors by directly targeting the oncogenes and tumour-suppressor genes, respectively (23-25).…”
Section: Introductionmentioning
confidence: 99%
“…27 Previous studies on specific cancer gene therapy paid close attention to tumour-selective delivery systems, but they had difficulties in achieving satisfactory effect because of side effects. 4,[28][29][30] We therefore proposed a new strategy to deal with the limitation from the use of vectors. The tumour-preferential Frizzled-7 promoter and Shiga toxin receptor The Frizzled-7 has been demonstrated as a critical receptor for the Wnt signalling and is involved in tumorigenesis and metastasis in many cancer types, including gastric cancer.…”
Section: Discussionmentioning
confidence: 99%